PENINGKATAN KETERSEDIAAN FISIK DAN WAKTU RATA-RATA ANTARA KEGAGALAN UNIT KOMATSU PC2000-8 PADA PT. UNITED TRACTORS, TBK DENGAN METODE FMEA - Rustanto Rustanto; Aditya Tirta Pratama; Anggi Febrianto; Firdaus Agung Syafutra; Willian Septianugraha; Badai Merdeka Walfitri (Jurnal Rekayasa Mesin, 2023)
The era of heavy equipment industry in Indonesia was begun   in the mid-1990s, by the first heavy equipment company, PT. United Tractors Tbk. This company have started heavy equipment sales and rental throughout Indonesia, which the well-known heavy equipment is the Hydraulic Excavator. It is used to excavate, rotate, move, load, mobilize and demobilize objects. Since the excavator was always used in the site’s daily operation, the number of failures is high, then the rate of excavator’s physical availability is below the requirement standard. The purpose of this study is to analyze the physical availability of the Komatsu Excavator Komatsu PC2000-8 by reducing the failure on the Boom Attachment by using the FMEA method. In order to obtain the optimum design and conditions as heavy machine, the analytical study was utilized for increasing physical availability on Hydraulic Excavators. According to the estimation of the analytical study, it was found that the highest physical availability of the PC2000-8 Hydraulic Excavator was at 98.4%, with the MTBF (Mean Time Before Failure) was at 269 hours.